In Vitro Methodologies for Evaluating Colon-Targeted Pharmaceutical Products and Industry Perspectives for Their Applications - Mauricio A. García; Felipe Varum; Jozef Al-Gousous; Michael Hofmann; Susanne Page; Peter Langguth (MDPI AG, 2022)
Several locally acting colon-targeted products to treat colonic diseases have been recently developed and marketed, taking advantage of gastrointestinal physiology to target delivery. Main mechanisms involve pH-dependent, time-controlled and/or enzymatic-triggered release. With site of action located before systemic circulation and troublesome colonic sampling, there is room for the introduction of meaningful in vitro methods for development, quality control (QC) and regulatory applications of these formulations. A one-size-fits-all method seems unrealistic, as the selection of experimental conditions should resemble the physiological features exploited to trigger the release. This article reviews the state of the art for bio-predictive dissolution testing of colon-targeted products. Compendial methods overlook physiological aspects, such as buffer molarity and fluid composition. These are critical for pH-dependent products and time-controlled systems containing ionizable drugs. Moreover, meaningful methods for enzymatic-triggered products including either bacteria or enzymes are completely ignored by pharmacopeias. Bio-predictive testing may accelerate the development of successful products, although this may require complex methodologies. However, for high-throughput routine testing (e.g., QC), simplified methods can be used where balance is struck between simplicity, robustness and transferability on one side and bio-predictivity on the other. Ultimately, bio-predictive methods can occupy a special niche in terms of supplementing plasma concentration data for regulatory approval.